2017
DOI: 10.1007/s10902-017-9846-1
|View full text |Cite
|
Sign up to set email alerts
|

Naked and Unashamed: Investigations and Applications of the Effects of Naturist Activities on Body Image, Self-Esteem, and Life Satisfaction

Abstract: Body image dissatisfaction is a serious, global problem that negatively affects life satisfaction. Several claims have been made about the possible psychological benefits of naturist activities, but very little empirical research has investigated these benefits or any plausible explanations for them. In three studies-one large-scale, cross-sectional study (n = 849), and 2 prospective studies (n = 24, n = 100) this research developed and applied knowledge about the possible benefits of naturist activities. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(56 citation statements)
references
References 54 publications
4
47
1
2
Order By: Relevance
“…Finally, the 5-item Satisfaction With Life Scale (Diener et al, 1985), which has been extensively used in prior research (Acun-Kapikiran, Korukcu, & Kapikiran, 2014;Swami, 2015;West, 2017), was used to measure participants' global life satisfaction. Participants indicated their agreement (1 = strongly disagree, 7 = strongly agree) with 5 items (α = .83):…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the 5-item Satisfaction With Life Scale (Diener et al, 1985), which has been extensively used in prior research (Acun-Kapikiran, Korukcu, & Kapikiran, 2014;Swami, 2015;West, 2017), was used to measure participants' global life satisfaction. Participants indicated their agreement (1 = strongly disagree, 7 = strongly agree) with 5 items (α = .83):…”
Section: Methodsmentioning
confidence: 99%
“…These findings are pertinent, as improved body image has been shown to promote life satisfaction through its positive impact on self-esteem (Acun- Kapikiran et al 2014;Kostanski and Gullone 1998;Olivardia et al 2004;Paradise and Kernis 2002;Park et al 2014;Pujols et al 2010). Whereas Swami (2016) found that women who regularly participated in drawing sessions that featured live (naked) models had higher body appreciation, as well as a lower drive for thinness and lower social physique anxiety, West (2017) found that participation in naturist activities tends to conduce to a more positive image of one's own body (whereby seeing others naked was found to be to be more important than being seen naked by others).…”
Section: Empirical Evidencementioning
confidence: 99%
“…A third source of support for the link between nudism and well-being is provided by empirical studies of the last few decades (e.g. Lewis and Janda 1988;Okami et al 1998;Okami 1995;Oleinick et al 1966;West 2017). Besides showing that exposure to (non-exhibitionist) public nudity lacks the detrimental psychological and behavioural effects commonly attributed to it, these studies have found that such exposure can have positive effects on well-being by promoting people's body image.…”
Section: Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Ungewitter (1913) in his nudity and culture book reported women were happier not feeling embarrassed about their bodies within naturist communities. The popularity of naturism is growing with up to a quarter of British people trying social nudity activities (West, 2018). Naturism has support from many governments in Europe and Scandinavia, most notably France where they promote benefits of respect for individual differences and body acceptance alongside collectivist benefits of spending time with family and friends in the most naturalistic environment possible (France, 2018a).…”
Section: What Is Naturism?mentioning
confidence: 99%